CO-PYROLYSIS CANGKANG KELAPA SAWIT DAN LIMBAH PLASTIK KEMASAN - Sabar Pangihutan Simanungkalit; Dieni Mansur (Widyariset, 2020)
In the present study, the co-pyrolysis of biomass waste, i.e. palm kernel shells (PKS) and industrial packaging plastic waste, namely polyethylene terephthalate (PET) and polyethylene (PE) were conducted. Prior to the pyrolysis, the raw materials were analyzed by thermogravimetric and elemental procedures. The pyrolysis was conducted in a fixed bed reactor which was heated from room temperature to 500 °C in an N2 atmosphere with a heating rate of 10 °C/min. The raw materials were weighted and mixed together manually with variations of weight composition ratios between biomass and plastic, i.e. 100% biomass (100/0); 90% biomass and 10% plastic (90/10); 70% biomass and 30% plastic (70/30); 50% biomass and 50% plastic (50/50); and 100% plastic (0/100). Then, they were put under pressure to obtain a pellet. The synergistic effect of biomass and plastic was investigated to see the difference between the pyrolysis products yields in theory and experiment. The bio-oil products were characterized by several methods and showed the potential to be used as a fuel. The optimum condition was obtained from 50/50 weight composition ratio. It was gained 30% improvement of the higher heating value of bio-oil, and the percentage area of hydrocarbon was contained in bio-oil increased from 4.68% to 53.40%.